ANALISIS KELAYAKAN FINANSIAL USAHATANI JAMBU BIJI KRISTAL (Psidium guajava L.) (Studi Kasus : Petani Jambu Biji Kristal di Desa Warisa Kecamatan Talawaan Kabupaten Minahasa Utara) - Sunarti Poppie S. Datundugon; Femi Hadidjah Elly; Jolanda Kitsia Juliana Kalangi (Sam Ratulangi University, 2020)
This study aims to determine the potential and opportunities for developing crystal guava farming and to analyze the financial feasibility of crystal guava farming in Warisa Village, Talawaan Sub-district, North Minahasa Regency. The study was conducted from July to October 2020. The selection of respondents was carried out by purposive sampling method. The research used primary data and secondary data. Primary data obtained from interviews, based on a questionnaire to one guava crystal farmer. Secondary data were obtained from the Head of Village Office, the Central Statistics Agency (BPS) and the Agriculture Office of North Minahasa Regency. The results showed that the potential of natural resources, namely the availability of land for the development of crystal guava cultivation is still quite extensive and the use of existing land can still be maximized. Warisa Village fulfills the growing requirements for the development of guava plants because it is located at an altitude of Â± 1-500 meters above sea level (masl), has a temperature of around 26.9-33,710 C in the daytime, rainfall is 1,993 mm year, type of soil is loose and fertile. Based on the financial feasibility analysis, Warisa Village's guava crystal cultivation is financially feasible to continue because it meets all investment criteria. *eprm*